Interculturality in St. Paul University Philippines - Allan Peejay M. Lappay (Randwick International of Social Science Journal, 2023)
This study discusses the interculturality of St. Paul University Philippines along its educational designs. Utilizing the descriptive research method and integral approach, it relates the convergence and the interaction of the members of the academic community with diverse profile manifested through their cultural backgrounds and faith affiliations. It also demonstrates SPUP’s practices along learning environment, policies and regulations, and programs and activities towards intercultural engagement. Lastly, it exhibits the ability of SPUP to foster a cultural experience integral of the Paulinian Core Values, namely: charity, charity, charism, commission, and Christ.